If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2g + 5h + 3g + -4g + -1h = 0 Reorder the terms: 2g + 3g + -4g + 5h + -1h = 0 Combine like terms: 2g + 3g = 5g 5g + -4g + 5h + -1h = 0 Combine like terms: 5g + -4g = 1g 1g + 5h + -1h = 0 Combine like terms: 5h + -1h = 4h 1g + 4h = 0 Solving 1g + 4h = 0 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-4h' to each side of the equation. 1g + 4h + -4h = 0 + -4h Combine like terms: 4h + -4h = 0 1g + 0 = 0 + -4h 1g = 0 + -4h Remove the zero: 1g = -4h Divide each side by '1'. g = -4h Simplifying g = -4h
| 11(20-x)=88 | | 5x-2[4x+3(x-1)]=3(10-x) | | 81=9(18-z) | | 8(25-q)=80 | | 1/8/1/3*22.5=x | | 28=7(15-q) | | 42=14(8-x) | | -5(2t-2)+7t=4t-7 | | 11(12-y)=110 | | 63=7(20-w) | | 12x^5+18x^3-8x^2-12=0 | | 4(8-b)=8 | | 7(8-c)=49 | | 12=4(6-u) | | 3b+6=-2b+7 | | 8X-4=6x | | 8y-7=y-4 | | 4a+12=-6a-13 | | =7-4i | | 8x+12=27x+1 | | 19=55-4q | | 12q+14=86 | | 111-9q=12 | | 4z/7-3=8 | | 4=100-8q | | 8q+39=63 | | 12x+44=9x+54 | | 3(3s+9)=81 | | 3a^2+1=2-2a | | 4/2*5-(9-6) | | 6(2l+6)=120 | | 8x+12=7x+35 |